Exploring Gender Differences in Motivation and Interest Towards English Language Learning: A Case Study of Islamic Secondary Schools Students in Sidoarjo - Nur Lailatul Mufidah; Fahmy Imaniar; Andriani Rachmania (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research studies the differences of males’ and females’ motivation and interest in learning English on 109 first-year students of one Islamic secondary school in Sidoarjo, East Java. It concentrates on four core points, there are intrinsic motivation, extrinsic motivation, individual and situational interest. By utilizing a descriptive quantitative approach with a descriptive statistical analysis, the findings reveal that the level of motivation of both groups of students is moderate to high average scores 3.4-4.2 on 5-point Likert scale. Females slightly outperformed males in intrinsic and extrinsic motivation, while males scored higher in personal and situational interest. This is consistent with Goal Orientation Theory, which clarifies that student learning motivation differs based on their learning goals (mastery vs. performance), as well as Expectancy-Value Theory, which states that engagement is shaped by the perceived value of English learning and expectations of success. The study recommends learning strategies that balance affective and instrumental aspects, as well as further studies using inferential analysis and longitudinal designs.